Lumut Daun Epifit Di Zona Tropik Kawasan Gunung Ungaran, Jawa Tengah - Mulyani, Eka; Perwati, Lilih Khotim; Murningsih, Murningsih (Departemen Biologi, Fakultas Sains dan Matematika, Universitas Diponegoro, 2014)
The tropical zone of Mount Ungaran is a tropical forest which are rich in diversity of flora. One of them is Bryophytes. Most of the Bryophytes of tropical forest are epiphytes. The largest group of Bryophytes is mosses (Bryophyta). However, research about epiphytic mosses in this area are sparse, so it is only a few information given about epiphytic mosses in this area. The aim of this research was to identify epiphytic mosses in tropical zone of Mount Ungaran altitudes 750, 980, and 1.100 meters above sea level, and also to determine the frequency attendance of species in this study site. This research was conducted in April through November 2012. Specimens was carried out at Laboratory of Ecology and Biosistematics, Department Biology, Faculty of Science and Mathematics, Diponegoro University, Semarang, Indonesia. The results shown there are 35 species mosses. Diversity of epiphytic moses most commonly found at altitude 1.100 meters above sea level, as many as 17 species, while at altitudes 750 and 980 meters above sea level was found 15 species. Family Hypnaceae is the family with highest number of species (6 species) and has highest total amount of frequency attendance by 16,13%. Hypnum plumaeforme and Luisierella barbula were the species which had wide distribution. Both of them were found at all three altitudes. Species with the highest total amount of frequency attendance is Hylocomium splendens from family Hylocomiaceae with total amount by 9,68%.Â Key words : epiphytic mosses, Mount Ungaran, tropical zone